The application of untargeted metabolomics coupled with chemometrics for the analysis of agitation effects on the sensory profiles of matcha tea - Siying Li; Hehe Tian; Guilong Zhu; Zhenbo Wei (Current Research in Food Science)
In the study, the effects of agitating parameters (different agitating rates and time) on the aroma and taste profiles of matcha tea were systematically investigated by the combination of untargeted metabolomics and chemometrics. The aroma profiles of matcha tea agitated at low rates (500 rpm) and for 30 s were more richness than that agitated with other parameters by sensory analysis and gas chromatography-ion mobility spectrometry. The key aroma compounds contributed to the sensory differences of matcha tea agitated at different rates and time were analyzed by gas chromatography-mass spectrometry and partial least square-discriminate analysis (PLS-DA), which were further verified by the triangle test. Thereinto, 2,4-decadienal associated with the sweet, brown and seaweed aroma significantly affected the aroma profiles of matcha tea with different agitating rates and time. The levels of bitterness and astringency were also higher in matcha tea with low agitating rates and time by sensory evaluation, which were attributed to the variations of phenolic compounds. Flavonol glycosides, gallic acid and (−)-gallocatechin were determined the key compound to the taste differences of matcha tea with different agitating parameters by the analysis of PLS-DA based on the results of high performance liquid chromatography and the sensory verification. And flavonol glycosides were mainly contributed to the bitterness and astringency, and gallic acid and (−)-gallocatechin influenced the umami and sweetness of matcha tea. Consequently, agitation has the potential to affect the sensory profiles of matcha tea by changing aroma and taste substances.